2019
DOI: 10.5114/fn.2019.85929
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Alzheimer’s disease

Abstract: Early reviews identified over 20 risk factors associated with Alzheimer's disease (AD) including age, familial inheritance, exposure to aluminium, traumatic brain injury (TBI), and associated co-morbidities such as vascular disease and infection. In the light of recent evidence, this review reconsiders these risk factors, identifies those currently regarded as important, and discusses various hypotheses to explain how they may cause AD. Rare forms of early-onset familial AD (EO-FAD) are strongly linked to caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
238
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 367 publications
(305 citation statements)
references
References 182 publications
3
238
0
7
Order By: Relevance
“…Aβ deposits were more likely to be distributed across all cortical layers in AD and especially in CTE. AD and CTE are both tauopathies, but CTE is associated specifically with TBI [30,34,44,[51][52][53]62] while the cause of sporadic AD is likely to be more complex [11], identifying this disorder as having the most widespread laminar degeneration among those studied. The distribution of the classic Aβ deposits may be of particular significance in CTE as it could reflect blood vessel damage [5].…”
Section: Discussionmentioning
confidence: 99%
“…Aβ deposits were more likely to be distributed across all cortical layers in AD and especially in CTE. AD and CTE are both tauopathies, but CTE is associated specifically with TBI [30,34,44,[51][52][53]62] while the cause of sporadic AD is likely to be more complex [11], identifying this disorder as having the most widespread laminar degeneration among those studied. The distribution of the classic Aβ deposits may be of particular significance in CTE as it could reflect blood vessel damage [5].…”
Section: Discussionmentioning
confidence: 99%
“…3 In this regard, individual life style factors, environmental stress and resultant 'allostatic load' has been suggested as a major influencing factors in the disease trajectory of AD. 4 In line with this stance, recent major trials reported significant benefits of lifestyle interventions in those with high risk of AD. 5 Among many lifestyle and nonpharmacological interventions frequently discussed, 6 physical exercise is increasingly accentuated as a potential therapeutic strategy for AD, 7 with its beneficial effects on mitochondrial function, brain plasticity, neurogenesis and cerebral blood flow.…”
Section: Introductionmentioning
confidence: 86%
“…Among the genetic risk factors, the presence of mutations on the Apolipoprotein E (APOE) gene correlates with a high probability of developing SAD [14,15]. The APOE gene has three variants, namely ε2, ε3, and ε4 that have different roles in AD pathogenesis.…”
Section: Sporadic Form Of Alzheimer's Diseasementioning
confidence: 99%